E-jurnal UPACARA FALE BENDERA FLAWA DI DESA WALSEKAT, KECAMATAN FENA LEISELA, KABUPATEN BURU, PROVINSI MALUKU (Perspektif Pendidikan Agama Hindu): UPACARA FALE BENDERA FLAWA DI DESA WALSEKAT, KECAMATAN FENA LEISELA, KABUPATEN BURU, PROVINSI MALUKU (Perspektif Pendidikan Agama Hindu) - ongen (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2024)
Abstract Hindu religious education should be carried out through religious ceremonies containing Hindu religious teachings to the younger generation, of course, non-formal education plays an important role in providing knowledge about divinity and moral values. As was done by the Hindu community in Walsekat Village, Fena Leisela District, Buru Regency, Maluku Province, where Hindu religious education was delivered through the Fale Bendera Flawa ceremony. The issues to be discussed include (1) The form of the Fale Bendera Flawa ceremony in Walsekat Village, (2) The function of the Fale Bendera Flawa ceremony in Walsekat Village, (3) What Hindu religious educational values are contained in the Fale Bendera Flawa ceremony in the Village? walsek. The theory used to analyze the problem is the structural-functional theory from Damar, the religious theory from Artadi, and the value theory from Yusnan. Data collection methods used are non-participant observation, unstructured interviews, documentation and libraries. The collected data were analyzed using descriptive analysis method with reduction steps, data presentation and conclusion. The results of the study showed (1) The form of implementation of the Flag of Flawa ceremony in Walsekat Village included 3 stages, namely the preparatory, peak (core) and closing stages. The preparatory stages include; ceremonial means, place and time, saints, the peak of the implementation includes; preparation of ceremonial facilities in the form of lofa, the main procession of the Fale Bendera Flawa ceremony, the final procession and closing of the implementation of the Fale Bendera Flawa ceremony, (2) The function of the Fale Bendera Flawa ceremony, in general in a religious ceremony is the implementation of Hindu religious teachings in religious life as a form of worship , trust and belief in Hyang Widhi (God), the functions of the Fale Bendera Flawa ceremony include; religious function, psychological function, structural social function, educational function and economic function, (3) The value of education is the most important part contained in a religious ceremony, ethical and cultural customs. The values of Hindu religious education contained in the Fale Bendera Flawa ceremony include; the value of religious education (belief), the value of nationalist education, the value of humanism education, the value of cultural education